Do Immediate Postoperative Radiographs Change Patient Management After Fracture Fixation? A Systematic Review. Issue 5 (May 2018) - Teo, Tammie; Schaeffer, Emily; Cooper, Anthony; Mulpuri, Kishore
Abstract : Objectives: To evaluate whether immediate (0–3 days) postoperative radiography leads to alterations in the management of patients postfracture fixation. Data Sources: Systematic review of English-language articles in the MEDLINE (1946–2016), EMBASE (1974–2016), CDSR (2005–2016), CENTRAL (1948–2016), and Google Scholar databases using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Study Selection: Randomized or non–randomized controlled trials and prospective or retrospective cohort studies that addressed surgical management of the upper extremity, lower extremity or hip fractures were eligible for review. All included studies needed to have performed radiography within 0–3 days of surgery and reported any directly resulting management changes. Data Extraction: Data were independently extracted by 2 reviewers using a standardized data collection form with predefined data fields for demographics, interventions, study methods, complications, and management outcomes. Data Synthesis: A random-effects model was applied, and pooled effects for absolute benefit increase (ABI) and number needed to treat (NNT) were calculated. Conclusions: Combining the 11/12 articles that reported by patient numbers, the ABI of immediate postoperative radiography for management change was 0.13% [95% confidence interval (CI), 0.00078%–0.60%; NNT = 753]. The ABI for identification of complications was 0.22% (95% CI, 0.0015%–1.24%; NNT = 453). Current literature suggests that immediate postoperative radiography does not lead to management change in most patients after fracture fixation. More comprehensive reporting, along with further prospective comparative research, is encouraged. Level of Evidence: Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.